A co-crystallization strategy toward high-performance n-type organic semiconductors through charge transport switching from p-type planar azaacene derivatives. Issue 7 (10th November 2021) - Wang, Zongrui; Li, Renping; Zhao, Kexiang; Yu, Fei; Zhao, Jianfeng; Zhen, Yonggang; Zhang, Qichun
Abstract : The co-crystallization strategy has offered an efficient route to achieve high-performance n-type semiconductors through charge-transport switching from pristine p-type azaacene derivatives. Abstract : In this work, we demonstrated that the co-crystallization strategy has offered an efficient and promising alternative route to achieve high-performance n-type semiconductors through charge-transport switching from pristine p-type systems. By using a simple "green synthesis" process through molecular "doping" with F4 TCNQ into a p-type planar azaacene derivative TMIQ (0.27 cm 2 V −1 s −1 ) host, charge transport characteristic switching occurs with a high electron mobility of 0.12 cm 2 V −1 s −1 under atmospheric conditions obtained for the D–A complex TMF4TQ (cocrystal). The reasons for such switching lie in the ingenious energy level and molecular packing arrangement tailoring. Specifically, the insertion of F4 TCNQ molecules has led to packing transformation from herringbone stacking (TMIQ) to a dense 2D brick arrangement and the low-lying LUMO levels (−4.55 eV) aligned to gold electrodes, thereby facilitating efficient electron injection and transport, and ensuring the air-stable nature, which is further confirmed using theoretical calculations. We believe that our work would provide new insights into high-performance air-stable n-type organic semiconductors exploration.